Ergonomic interventions: comparisons between footrest and anti-fatigue mat in reducing lower leg muscle discomforts during prolonged standing - Omar, Noreen Adila; Karuppiah, Karmegam; How, Vivien; Perimal, Enoch Kumar; Sambasivam, Sivasankar; K. C. Mani, Kulanthayan (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2019)
Ergonomics is a science focusing on the study of human fit, decreasing human fatigue and discomfort through the design of new product. Prevention related to workers injury and illness such as muscle discomfort is part of the main goals in ergonomics interventions. Thus, this present study investigates the effectiveness of ergonomic interventions such as footrest and floor conditions in reducing workers lower leg muscle discomforts during prolonged standing. The main objective of this study was to determine and compare the lower leg muscles discomfort (exertion percentage (%)) of Gastrocnemius and Tibialis Anterior among the respondents using the two ergonomic interventions (footrest and anti-fatigue mat). About 60 healthy subjects were recruited to stand for 2 hours (120 minutes) while using the two interventions in different session with one week interval between each test session. During standing, lower leg muscle discomfort of Gastrocnemius and Tibialis Anterior muscles were continuously monitored. Changes in lower leg muscle discomforts over standing time were measured using the surface Electromyography (sEMG). In this study, the sEMG readings showed that the percentage of exertion (%) were increasing with time (within 120 minutes) on muscles for both legs with the usage of the interventions (footrest and anti-fatigue mat). However, the percentage of exertion (%) from the sEMG readings were lower compared to previous studies. The independent t-test was used to find the mean changes on exertion percentage (%) between each muscles of both legs for the two interventions. Results found that there were significant exertion percentage at certain time with 15 minutes time period within the 120 minutes standing. This study showed that the ergonomic interventions (anti-fatigue mat and footrest) gives a low number of exertion percentage (%), showing a reduced muscle discomfort to the lower leg muscles compared to previous studies and interventions. In comparisons with footrest, this study showed that anti-fatigue mat is more applicable for the assembly workers in the industrial factory. The data produced by the comparisons between the two interventions can be useful especially to the Department of Occupational Safety and Health Malaysia (DOSH) in enhancing the safety and wellbeing of industrial workers in Malaysia.